Upaya Peningkatan Pengetahuan tentang Diet Hipertensi pada Lansia - Farhani, Muhammad Fatih; Maryoto, Madyo; Sumarni, Tri (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Hypertension is a condition characterized by an increase in blood pressure that forces the heart to work harder and often occurs without noticeable symptoms, hence it is known as “The Silent Killer.” One of the preventive and management efforts for hypertension is through dietary modification by regulating eating patterns and limiting the consumption of salt, preserved foods, soft drinks, coffee, tea, and alcohol to help lower blood pressure. Objective: This community service activity aimed to increase the knowledge of elderly individuals at the Baseh Village Elderly Health Center regarding the hypertension diet and healthy lifestyle practices. Method: The implementation involved lectures and discussions accompanied by a pre-test and post-test to measure participants’ knowledge. Knowledge was assessed using a structured questionnaire consisting of multiple-choice questions covering the definition, risk factors, prevention, and dietary management of hypertension. The questionnaire was reviewed for content validity by public health experts. The intervention was conducted in one session lasting approximately 60 minutes and involved 25 elderly participants. Blood pressure was measured before and after the educational intervention using a calibrated sphygmomanometer to assess physiological changes. Result: The pre-test results showed that 40% of participants had good knowledge, 52% had sufficient knowledge, and 8% had poor knowledge. After the education session, 80% demonstrated good knowledge and 20% had sufficient knowledge. Blood pressure measurements showed a decrease in the number of participants with stage 1 hypertension from 13 to 6 people and an increase in the pre-hypertension category from 12 to 19 people. Conclusion: Health education through lectures and discussions effectively increased knowledge about hypertension and contributed to lowering blood pressure by encouraging healthy lifestyle changes among elderly participants.